In-between Figure Working in a Precarious Field: Re-engaging with Notions of the Dramaturg - Gade, Solveig (Nordic Theatre Studies, 2019)
This essay is preoccupied with a notion that is often embraced in theatre and performance theory: that of the dramaturge as a flexible, in-between figure. Taking into consideration, however, the precarious working and living conditions that freelance dramaturgs are typically subjected to as well as the structural parallels between the flexible dramaturg and the ideal of the agile post-Fordist employee, the article sets out to critically investigate the concept of inbetween-ness. Theoretically, the essay draws on theory formations from theatre and performance theory on new dramaturgies as well as theories from political theory and performance theory concerning the precarious working conditions experienced by a majority of cultural workers today. Empirically, the essay builds on two surveys conducted amongst dramaturgs working in the field of Danish theatre and dance with a view to shedding light on their working conditions, particularly with regards to wages and credit policy. The data obtained in the two surveys is analysed and discussed against the background of the two theoretical strands laid out in the first part of the article. In conclusion, the article ventures the claim that if we wish to create sustainable working conditions for dramaturgs, especially those working on a freelance basis, we need to critically address not only their actual working conditions, but also the notions and concepts through which dramaturgs tend to self-identify.